Benefits of language tourism for ukrainian students - Kovalchuk, Olga (My University, 2016)
The paper discusses current issues associated to language tourism relying upon the data reviewed in order to define its value for the language learners. Secondly it provides analysis of leading Ukrainian agencies which offer language tours abroad. Lastly, the research studies the effects in language learning.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; language tourism; foreign languages; english; мовний туризм; іноземні мови; англійська мова